Market Reactions To Domestic And Global Policy Events: An Event Study Of The Indonesian Capital Market In Early 2025 - Said Aryonindito; Saskia Salmana Dahyar; Adisti Gilang Cempaka; Vecco Suryahadi Saputro (CV Putra Publisher, 2025)
This study examined the reactions of the Indonesian capital market to selected domestic and global policy events during January–February 2025, a period marked by the early phase of a new administration and heightened policy uncertainty. Using an event study approach, the analysis focused on five key events: the implementation of the Biodiesel B40 policy, the announcement of a foreign exchange retention requirement for export earnings, the Federal Open Market Committee (FOMC) statement, the release of January 2025 inflation data, and Bank Indonesia’s monetary policy decision. Results indicated that the Biodiesel B40 policy and low inflation release generated positive sentiment, reflected in rising prices, higher trading activity, and increased foreign buying. Conversely, the export earnings retention policy triggered negative market responses, particularly increased foreign selling in export-oriented sectors. Findings suggested that the market displayed characteristics of semi-strong form efficiency, responding promptly to public information but with some delayed adjustments. The study concluded that both domestic and global policy events significantly shaped short-term market dynamics, though reactions varied by event type. Future research was recommended to employ statistical tests on abnormal returns and trading activity for stronger empirical validation